An insight into space and remote sensing technologies concerning agriculture and landscape analysis - Cuca, Branka; Barazzetti, Luigi; Brumana, Raffaella; Previtali, Mattia (My University, 2015)
Remote sensing and space technologies are increasingly called to offer innovative solutions for current challenges induced by climatic and global change. One of the main priorities of the European Space Policy regards the economic independence of the old continent in this sector. In terms of research and innovation this inevitably leads to numerous attempts in having independent market of services that would tackle specific needs of the citizens. Agriculture, for example, is one of the sectors majorly subsidized by European funds on national, regional and local level, with the aim to foster a more productive and sustainable development. Due to a large territorial scale at which agricultural phenomena are observed, and thus the spatial resolution required, it is also one of the main sectors that has been monitored from space over the past 30 years. In fact, one of the main missions of USA Landsat satellites was to provide a continuous and systematic overview of the globe for the purposes of an effective monitoring of the environment. This paper represents an overview of the ongoing initiatives in Space research done for the field of agriculture and landscape monitoring. In particular, the paper looks into the future possibilities that will be offered by full, open and free-of-charge data arriving from ongoing Copernicus missions and the contribution of Sentinel satellites to the agricultural sector.
Keywords: Agriculture; Landscape analysis; Remote Sensing; Satellite imagery; Sentinel missions